2008
DOI: 10.4000/quaternaire.3092
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene eruptive chronology of the Gölcük volcano, Isparta Angle, Turkey. Chronologie des épisodes volcaniques pléistocènes du volcan Gölcük, Angle d’Isparta, Turquie

Abstract: Pleistocene eruptive chronology of the Gölcük volcano, Isparta Angle, Turkey Chronologie des épisodes volcaniques pléistocènes du volcan Gölcük, Angle d'Isparta, Turquie

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 9 publications
0
28
0
2
Order By: Relevance
“…The Gölcük volcanics outcrop mainly in the south of Isparta settlement area, but small extrusions are also observed in the western and northern sides (figure 1). Platevoet et al (2008) separated the Gölcük volcanics into two major stages:…”
Section: Geological Settingmentioning
confidence: 99%
“…The Gölcük volcanics outcrop mainly in the south of Isparta settlement area, but small extrusions are also observed in the western and northern sides (figure 1). Platevoet et al (2008) separated the Gölcük volcanics into two major stages:…”
Section: Geological Settingmentioning
confidence: 99%
“…1), situé au sud de la ville d'Isparta (Turquie), est un volcan composite, construit en trois phases lors du Pléistocène (Alici et al, 1998;Platevoet et al, 2008;Elitok et al, 2010 et al, 2014). le magma lors de sa remontée en surface.…”
Section: -Une Remise En Question Des âGes K-ar Des Dômes Trachytiquesunclassified
“…This layer resulted from an eruption that resulted in equivalents deposits 25 km from the Gölcük volcano which is situated some 25 km to the West. The eruption is probably related to the growth of the last trachytic domes that have been found (Platevoet et al, 2008). Kazanci (1993) indicated that, south of Lake Egirdir, pyroclastic-fall sediments occur within the successions of alluvial cones that advance toward the lake, and that these pyroclastics are products of the Pliocene Gölcük (Isparta) volcanism, thus implying that the lake basin developed prior to the middle-late Pliocene.…”
Section: Previous Researchesmentioning
confidence: 99%
“…More research has been carried out on a wide range of geological topics concerning Lake Egirdir and its surroundings (Poisson, 1984;Boray et al, 1985;Yağmurlu & Karaman, 1987;Karaman, 1988Karaman, , 1989Hançer & Karaman, 1991, 1993Yağmurlu, 1991;Kibici et al, 1993;Barka et al, 1995;Poisson et al, 2003;Platevoet et al, 2008).…”
Section: Previous Researchesmentioning
confidence: 99%